Comparative activities of the beta-lactamase inhibitors YTR 830, clavulanate, and sulbactam combined with ampicillin and broad-spectrum penicillins against defined beta-lactamase-producing aerobic gram-negative bacilli. - Jacobs, M R (1986)
The in vitro synergistic activities of the beta-lactamase inhibitors YTR 830, clavulanate, and sulbactam, combined with ampicillin, ticarcillin, mezlocillin, azlocillin, piperacillin, and apalcillin, were determined against 34 strains of members of the Enterobacteriaceae family, Pseudomonas aeruginosa, Aeromonas hydrophila, and Haemophilus influenzae with characterized plasmid or chromosomal beta-lactamases or both. Strains were tested against fixed concentrations of beta-lactamase inhibitors (8 micrograms/ml) combined with doubling dilutions of beta-lactams. Synergy was defined as a fourfold or greater decrease in the MIC of the beta-lactam. Against Enterobacteriaceae producing Richmond and Sykes class III and V plasmid-mediated beta-lactamases, synergy was obtained against most strains with YTR 830- and clavulanate-beta-lactam combinations, with sulbactam being less effective. Against Enterobacteriaceae producing class I chromosomal beta-lactamases, combinations containing YTR 830 or sulbactam were more synergistic than combinations containing clavulanate. Against strains producing class V PSE enzymes, all three inhibitors were synergistic with piperacillin and apalcillin against strains producing PSE-1, -3, and -4 enzymes, while the PSE-2-producing strain was resistant to all inhibitors. YTR 830-beta-lactam combinations were also synergistic against strains producing the novel beta-lactamases OHIO-1, TLE-1, AER-1, and ROB-1. Overall, YTR 830 with piperacillin or apalcillin was the most effective combination.